Translating theoretical perspectives into constructive debate: Reconceptualising the curriculum in the South African context - Clarence-Fincham, Jenny; Naidoo, Kibashini (South African Journal of Higher Education, 2016)
In the context of the complex challenges facing higher education, this paper aims to illustrate how the translation of theoretical insights into a carefully formulated set of questions, can function as a flexible, discipline-specific developmental framework for curriculum development. Drawing primarily on Bernstein’s concept of the pedagogical device and also on the work of Maton and Muller (2007), Muller (2008), Young (2008), and Wheelahan (2010), the authors argue that this process, without either alienating or patronising staff has the potential to strengthen the theoretical understanding of their curricula by raising awareness about differentiated knowledge domains and the extent to which this impacts on curriculum design. This facilitates a collaborative process of critical discussion and debate which highlights the importance of access to knowledge, encourages exploration of the nature of disciplines, their shaping values, the kinds of curricula that emerge from them and the associated student and staff identities.